Harnessing indigenous knowledge in disaster risk management in Aotearoa New Zealand (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. This paper will provide an insight into understanding of risks and cultural heritage by local and indigenous communities, as well as their knowledge, values and practices informing the perception of disaster risk management. The aim is to contribute to the implementation of Community Based Disaster Risk Management (CBDRM), which leads to a locally appropriate and locally "owned" strategy for disaster risk management. Approach. The paper presents experiences in disaster response by local communities in New Zealand Aotearoa and consequent shift in the perspective towards disaster risk management which needs to be reflected in cultural heritage field. Disaster risk management plans can be understood as series of written policies and procedures that prevent or minimize damage resulting from disasters, tailored to a museum’s, library’s, archives or community’s specific circumstances and facilities. Having a disaster management plan is not an end result, in itself. The process of creating, implementing, and updating a plan can be far more important and beneficial to an institution or community. Value. At-risk communities are actively engaged in the identification, analysis, treatment, monitoring and evaluation of disaster risks in order to reduce their vulnerabilities and enhance their capabilities. This means people are at the heart of decision-making and implementation of disaster risk management activities. This aligns with a paradigm shift in disaster management from having management agencies as the primary actors, towards wider and deeper stakeholder involvement, especially in the private sector with local level actors.
Keywords: community based disaster risk managemet (CBDRM); disaster planning for cultural heritage; indigenous knowledge